Radiative Heat Transfer in Models of DC Arc Plasma - Baeva, Margarita; Kloc, Petr; Cressault, Yann (Czech Technical University in Prague, 2023)
The radiative heat transfer in arc plasma models of a free-burning arc and a plasma torch in atmospheric pressure argon is taken into account in a self-consistent way. This is realized by the P1 method for solving the equation of radiative transfer and the multi-band approximation that considers the division of the emitted spectrum into a number of spectral bands. Net emission coefficients are evaluated by solving the equation of radiative transfer in three dimensions in an isothermal cylindrical plasma. The arc plasma parameters of the free-burning arc and the plasma torch obtained accounting for radiative transport have been compared with those from the temperature-dependent net emission coefficient for a radius of 1 mm. The results show that in general, the models applying the net emission coefficient provide results in the arc core close to that using the P1 method. The discrepancy is stronger in the arc periphery and near walls, where the P1 method predicts absorption of radiation.

The radiative heat transfer in arc plasma models of a free-burning arc and a plasma torch in atmospheric pressure argon is taken into account in a self-consistent way. This is realized by the P1 method for solving the equation of radiative transfer and the multi-band approximation that considers the division of the emitted spectrum into a number of spectral bands. Net emission coefficients are evaluated by solving the equation of radiative transfer in three dimensions in an isothermal cylindrical plasma. The arc plasma parameters of the free-burning arc and the plasma torch obtained accounting for radiative transport have been compared with those from the temperature-dependent net emission coefficient for a radius of 1 mm. The results show that in general, the models applying the net emission coefficient provide results in the arc core close to that using the P1 method. The discrepancy is stronger in the arc periphery and near walls, where the P1 method predicts absorption of radiation.
Radiative Heat Transfer in Models of DC Arc Plasma
Keywords: radiative heat transfer; arc plasma; equilibrium; multi-band approximation; P1 method; net emission coefficient; radiative heat transfer; arc plasma; equilibrium; multi-band approximation; P1 method; net emission coefficient